2020
DOI: 10.1002/fsn3.1382
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical immunosensor based on carboxylated single‐walled carbon nanotube‐chitosan functional layer for the detection of cephalexin

Abstract: In this study, a sensitive and selective electrochemical immunosensor for cephalexin (CEX) determination on a glassy carbon electrode (GCE) surface was modified by a carboxylated single‐walled carbon nanotubes/chitosan (SWNTs‐COOH/CS) composite. The SWNTs‐COOH/CS composite was used to enhance sensor performance and to enlarge the electrochemical response of CEX. The cephalosporin‐ovalbumin coupling (CEX‐OVA) was synthesized using the reactive ester method. The free CEX in solution could be effectively measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Yu et al (2020) reported that the binding of CNTs to CHI occurs through adsorption by the carboxyl groups of the CNTs to the amine groups of the CHI. Although a uniform nanocomposite was observed, forming a homogeneous film with a greater surface area at the expense of the nanomaterial, the insulating nature of the CHI was predominant and therefore reduced the electrocatalytic activity [ 40 ]. To promote electrocatalytic activity by the adsorption of a redox species to the film, PB was added to the CHI–CNT film, and the synthesis was carried out in two ways, either by mixing the three compounds simultaneously or by adding the PB after the dispersion of the compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al (2020) reported that the binding of CNTs to CHI occurs through adsorption by the carboxyl groups of the CNTs to the amine groups of the CHI. Although a uniform nanocomposite was observed, forming a homogeneous film with a greater surface area at the expense of the nanomaterial, the insulating nature of the CHI was predominant and therefore reduced the electrocatalytic activity [ 40 ]. To promote electrocatalytic activity by the adsorption of a redox species to the film, PB was added to the CHI–CNT film, and the synthesis was carried out in two ways, either by mixing the three compounds simultaneously or by adding the PB after the dispersion of the compounds.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the analytical performance of some previously reported methods in addition to the proposed CL method for determination of CEF are summarized in Table 2. The analytical figures of merit of the proposed method are superior to amperometry [3] , spectrophotometry [6] , and CE [8] and are inferior to DPV [4] , potentiometry [5] , HPLC [7] ,…”
Section: Optimizationmentioning
confidence: 99%
“…reactions used in CL methods for determination of CEF are [Ru (bpy) 3 ] 2+ -KMnO 4 [10] , glyoxal-KMnO 4 [11] , and luminol-KIO 4 . [12] In all of these CL reactions, the onset of the reaction depends on adding an external oxidant, including KMnO 4 or KIO 4 . The luminol-O 2 CL reaction is a reaction in which only dissolution of luminol in an alkaline solution is sufficient for the CL reaction to occur.…”
mentioning
confidence: 99%
“…To date, different detection methods have been developed for cephalexin, including chromatography, 1,2 colorimetry, 3,4 spectrometry, [5][6][7][8] and electrochemical. [9][10][11] Among these methods, the electrochemical approach can be a proper candidate owing to its simplicity, high speed, high sensitivity and selectivity, cost efficiency, and low-amount detection ability. 12 Given the aforementioned benefits, researchers are increasingly using the electrochemical detection of different drugs in solution media.…”
Section: Introductionmentioning
confidence: 99%